Necrotizing Soft-Tissue Infections: A Retrospective Review of Predictive Factors for Limb Loss - Park, Hee-Gon; Yang, Jong-Heon; Park, Byung-Hoon; Yi, Hyung-Suk (Clinics in orthopedic surgery, 2022)
Emergent diagnosis and treatment are important for the survival of patients with necrotizing soft-tissue infections (NSTIs). Death is the most catastrophic outcome, but limb loss is also one of the most important complications that can have a significant impact on the rest of the patient's life. The purpose of this study was to identify predictive factors for limb loss caused by NSTIs. The data of patients at our center who were diagnosed with NSTIs from May 2003 to January 2019 were analyzed retrospectively. The inclusion criteria were patients with a definite diagnosis of NSTI involving the upper or lower limb. A total of 49 patient records were analyzed in terms of demography, laboratory data, microbiological causes, treatment, and final outcome. Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) scores at initial admission were also collected as laboratory data. Final outcomes were classified into survival with limb salvage and survival with limb loss. The limb loss rate was 20.4% (10/49) in our study. On comparison between the limb salvage group and the limb loss group, independent risk factors of limb loss were as follows: presence of hypotension at admission (odds ratio [OR], 8.2; 95% confidence interval [CI], 1.7-38.3; = 0.008); LRINEC score ≥ 9 (OR, 5.8; 95% CI, 1.3-25.6; = 0.012), and glucose level > 300 mg/dL (OR, 4.5; 95% CI, 0.9-21.9; = 0.041). Various microbiological organisms were isolated; the most prevalent specimen was streptococci (32.6%), followed by staphylococci (26.5%). Poor outcomes including limb loss and mortality had no correlation with microbiological organisms. For patients with NSTIs, the presence of hypotension at admission, a high glucose level (> 300 mg/dL), and a high LRINEC score (> 9) were independent risk factors for limb loss.